SARS-CoV-2 Variants and Efficacy of Available COVID-19 Vaccines - Cheepsattayakorn A; Cheepsattayakorn R (Achievements and Challenges of Medicine and Medical Science Vol. 1, 2024)
SARS-CoV-2 (COVID-19) variants of concern might be related to changes in both morbidity and mortality. Changes in both morbidity and mortality in COVID-19-infected individuals may be due to suppression of the host immune response, altered viral transmission dynamics, or higher viral loads that might worsen the clinical outcomes. Identification and analysis of currently available COVID-19 vaccines against SARS-CoV-2 (COVID-19) variants of concern, efficacy, and adverse events are the objective of this study. The current variants of concern, lineages B.1.351, B.1.1.7, and P1 affect the function of the spike protein and other SARS-CoV-2 proteins and can alter interaction with hACE2. The first three COVID-19 vaccines expressing spike protein and a progressing national rollout have authorization for emergency use in the United Kingdom (UK) and demonstrated protection against COVID-19 and decreased transmission after vaccination in the preliminary report. The search was applied to the articles that were published between 2020 and 2023. The chosen keywords for developing this study were “SARS-CoV-2” or “COVID-19” or “Variants” “Vaccine Efficacy” or “Vaccine Adverse Events With strict literature search and screening processes, it yielded 14 articles (2020 = 2; 2021 = 10 articles; 2023 = 2 articles) from 400 articles of initial literature database (2020-2023). A study demonstrated in early March 2021 the efficacy of various COVID-19 vaccines produced by many manufacturers in symptomatic SARS-CoV-2 (COVID-19) patients and patients infected with SARS-CoV-2 (COVID-19) variants as the following products (vaccine name), used technology, doses, efficacy against symptomatic disease, and efficacy against variants (B.1.1.7 (first detected in the United Kingdom) and B.1.351 (first detected in South Africa)). It is hard to predict the long-term risk of immune escape. From experience with avian coronavirus, vaccines against one variant will protect against similar variants, but not always against highly divergent variants. As SARSCoV-2 (COVID-19) variants are too divergent, similar to flu vaccines, COVID-19 vaccines will be changed. In conclusion, modifying COVID-19 vaccines would probably be the most straightforward step in involving SARS-CoV-2 (COVID-19) variants. As SARS-CoV-2 (COVID-19) variants are too divergent, similar to flu vaccines, COVID-19 vaccines will be changed. It might be more robust that multivalent vaccines include the viral nucleoprotein in the long term. More challenging will be deciding when and how to deploy COVID-19 vaccines 2.0.